Arduino-Based Novel Hardware Design for Liquid Helium Level Measurement. (October 2018) - Khan, Pathan Fayaz; Sengottuvel, S.; Patel, Rajesh; Mani, Awadhesh; Gireesan, K.
Liquid helium (LHe) is used as a cryogen in a variety of applications involving superconductivity and is routinely monitored for conducting low-temperature experiments. Thermoacoustic oscillations, which are inevitably present inside closed LHe containers, are utilized for level detection by sensing the vibrations at the warm end of a thin capillary tube inserted into the Dewar. The position of the capillary tube at which a sudden change occurs in these oscillations is manually sensed to identify the liquid level. The present work proposes a novel hardware design to identify the thermoacoustic oscillations in a reliable way using an accelerometer driven by an Arduino microcontroller. Further, an automated approach has been devised to quantify the rate of change of these helium oscillations to measure the LHe level. The proposed method has been tested during several trials on a 120 L and 100 L capacity Dewar using the proposed hardware, and the mean error in measuring the LHe level was calculated to be less than 1 cm in comparison with the gold standard niobium-titanium level sensor. The results encourage the use of the proposed method to evolve as a cost-effective alternative to the widely used superconducting level sensors in measuring LHe level.